MORPHOLOGICAL CHANGES OF PLACENTA IN CHILDBIRTH WEAKNESS OF LABOR ACTIVITY - Udovytska, N.A. (World of Medicine and Biology, 2016)
The paper presents the morphological characteristics of the placenta in women, childbirth is complicated by the weakness of labor in comparison with the case of a normal course of labor.